An event-related potentials study of biological motion perception in humans - Hirai, Masahiro; Fukushima, Hirokata; Hiraki, Kazuo (Neuroscience letters, 2003)
In order to clarify the neural dynamics involved in the perception of biological motion, we recorded event-related potentials from 12 subjects. The subjects were shown biological motion or scrambled motion as a control stimulus. In the scrambled motion, each point had the same velocity vector as in the biological motion, but the initial starting positions were randomized. The perception of both biological and scrambled motion elicited negative peaks at around 200 (N200) and 240 ms (N240). Furthermore, both negative peaks were significantly larger in the biological motion condition than in the scrambled motion condition over the right occipitotemporal region. In light of previous human neuroimaging studies, we speculate that component N200 is generated near the extrastriate cortex area and N240 is generated from the superior temporal sulcus region.